Transformation of plants and soil microorganisms - Herrera-Estrella, Alfredo; Van Montagu, Marc; Wang, Kan 1959- (Cambridge University Press, 1995)
Over the past fifty years plant breeders have achieved impressive improvements in yield, quality and disease resistance. These gains suggest that many more modifications might be introduced if appropriate genes can be identified. Current DNA techniques allow the construction of transgenic plants and this important new book reviews the current state of knowledge. A team of leading researchers provide in-depth reviews at the cutting edge of technology for laboratory techniques for the transformation of important soil microorganisms and recalcitrant plants of economic value. The book is divided into three sections: soil microorganisms; cereal crops; and industrially important plants. The most effective methods used to date are compared, and their merits and limitations discussed. Some chapters emphasise case studies and applications. In cases where obstacles remain to be overcome, an overview of progress to date is given. The book will serve as a general guide and reference tool for those working on transformation in microbiology and plant science.